2022
DOI: 10.21511/ppm.20(2).2022.38
|View full text |Cite
|
Sign up to set email alerts
|

The influence of technological innovative capabilities on firm performance: Moderating effect of strategic agility

Abstract: This study investigates the influence of technological innovative capabilities (TICs) on firm performance (FP) in the IT sector, with strategic agility as a moderator variable. This paper analyzes the TICs at the firm level in the service sector using the functional approach. An online structured questionnaire was adapted and refined to collect the required information on the influence of TICs dimensions on FP in the IT sector to achieve the objectives. The unit of analysis consists of top management staff and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…One of the primary moderating control factors is the firm size. Firm size is viewed as one of the most validated core factors in determining a company's performance in terms of its effect on competitive market power (Ural and Acaravci, 2006;Wolff and Pett, 2000;Wang, 2018). Larger firm size affords companies several economic benefits, mainly through economies of scale, minimization of operational costs, and production cost efficiency compared to small-sized firms.…”
Section: Other Business and Operational Strategic Factorsmentioning
confidence: 99%
“…One of the primary moderating control factors is the firm size. Firm size is viewed as one of the most validated core factors in determining a company's performance in terms of its effect on competitive market power (Ural and Acaravci, 2006;Wolff and Pett, 2000;Wang, 2018). Larger firm size affords companies several economic benefits, mainly through economies of scale, minimization of operational costs, and production cost efficiency compared to small-sized firms.…”
Section: Other Business and Operational Strategic Factorsmentioning
confidence: 99%
“…Investment Management and Financial Innovations, Volume 19, Issue 4, 2022 http://dx.doi.org/10.21511/imfi.19 (4).2022. 15 Notably, the financial literature has paid a special attention to financial performance as a key internal manipulation mechanism, and to its effects on earnings management (Zang, 2012;Kothari et al, 2015;Jiang et al, 2018;Khraim, 2022;Garfatta et al, 2022;Pham, 2022). Few studies examined directly the relationship between earning management and performance in developing economies.…”
Section: Introductionmentioning
confidence: 99%
“…Using a distinct and causal research design, they found that research and development capacity significantly affected the value generation in these SMEs. This study focused on manufacturing SMEs, with a specific geographic scope, suggesting that technological innovation positively impacts their performance Khraim (2022). explored the effect of technological innovation capabilities on firm performance in the IT sector, with strategic agility as a moderating variable.…”
mentioning
confidence: 99%
“…pp:(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), Month: May -August 2024, Available at: https://researchbridgepublisher.com/2.3.1Review of the study Literature…”
mentioning
confidence: 99%
See 1 more Smart Citation